2020
DOI: 10.1021/acssuschemeng.0c06736
|View full text |Cite
|
Sign up to set email alerts
|

Green Fabrication of High-Performance Chitin Nanowhiskers/PVA Composite Films with a “Brick-and-Mortar” Structure

Abstract: Chitin is a biobased and renewable biopolymer which consistents with the green and sustainable development. However, the strong inter-and intra-molecular hydrogen bonding interactions of chitin endow it with very poor solubility and processability, which extremely limit its broad application. In this work, a simple "building block reorganization" strategy has been developed to prepare chitin-based composite film with a "brickand-mortar" structure. After successively experiencing salt-induced "preaggregation" a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 36 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…The poor solubility of the polymer in water was due to the strong hydrogen-bond interaction among the polymer moieties (−P­(O)­CH 2 OH) and also to hydrophobic polystyrene-like backbones. The similar phenomenon was also found when dissolving other hydroxyl-rich polymers such as cellulose, polyvinyl alcohol, and chitin in water . The main-chain of hydroxyl-rich polymers was stabilized by strong and complex intramolecular and intermolecular hydrogen-bond networks.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The poor solubility of the polymer in water was due to the strong hydrogen-bond interaction among the polymer moieties (−P­(O)­CH 2 OH) and also to hydrophobic polystyrene-like backbones. The similar phenomenon was also found when dissolving other hydroxyl-rich polymers such as cellulose, polyvinyl alcohol, and chitin in water . The main-chain of hydroxyl-rich polymers was stabilized by strong and complex intramolecular and intermolecular hydrogen-bond networks.…”
Section: Resultssupporting
confidence: 70%
“…The similar phenomenon was also found when dissolving other hydroxyl-rich polymers such as cellulose, 51 polyvinyl alcohol, 52−54 and chitin in water. 55 The main-chain of hydroxyl-rich polymers was stabilized by strong and complex intramolecular and intermolecular hydrogen-bond networks. The existence of hydrogen-bond interaction was studied by variable temperature FT-IR spectroscopy (Figure S10).…”
Section: Normal Free-radical Solution Polymerization Of Vbzbhpomentioning
confidence: 99%
“…In particular, the films exhibited low coefficient of thermal expansion (Figure b) . Biocompatible poly­(vinyl alcohol) has been integrated with nanochitin in environmentally friendly films for improved performance. , …”
Section: Applications Of Nanochitin In Multidimensional Materialsmentioning
confidence: 99%
“… 64 . Shi et al 65 reported a “building block reorganization” strategy to prepare chitin‐based DN film. In this system, chitin nanowhiskers (ChNWs) and PVA served as “bricks” and “mortar”, respectively.…”
Section: Design and Preparation Of Pdn Hydrogelsmentioning
confidence: 99%
“…61 and the "bottom-up" method (e.g., wet-spinning method, 62 self-assembly method, 63 and dissolution-regeneration method, etc.). 64 Shi et al 65 reported a "building block reorganization" strategy to prepare chitin-based DN film. In this system, chitin nanowhiskers (ChNWs) and PVA served as "bricks" and "mortar", respectively.…”
Section: Chitin-based Dn Hydrogelsmentioning
confidence: 99%